A systematic framework for prioritizing farmland preservation - Machado, E. A.; Stoms, D. M.; Davis, F. W. (National Center for Ecological Analysis and Synthesis, 2003)
The California Legacy Project (CLP) mission is "to enable the state and its partners in conservation to develop and implement a strategic and inclusive approach to conserving and restoring California's lands and natural resources." In 2001 The Resources Agency of California contracted with the National Center for Ecological Analysis and Synthesis at UC Santa Barbara to convene a working group to help bring systematic conservation planning theory and methods to bear on the design and implementation of CLP. The conservation planning framework for farmland described in this report for is one of the products from that working group. The framework is intended to serve the dual purpose of helping decision makers to evaluate current opportunities (e.g., current proposal applications for State conservation funds) and to help planners develop longer term conservation strategies that highlight areas for more focused analysis and collaborative planning. We do not present a plan or "blueprint" for future conservation activities. Instead, we offer an analytical, data-driven planning process that could be applied to ongoing conservation assessments and evaluations by State conservation planning staff and collaborating organizations over the State or regions of the State. We organize the planning framework based on a hierarchy of conservation goals and objectives, each of which is further elaborated in terms of specific objectives, criteria, and sources of evidence. For farmland preservation, we summarize these goals as retaining farmlands: 1) with the greatest sustained production capacity, 2) that provide high amenity values (e.g., habitat, open space, floodplain management, and scenic values), and 3) whose location reduces the risk of urban sprawl. The framework applies GIS technology to map farmland conservation value and investment priorities based on available spatial data, derived indices and simple algebraic functions. A planning region is divided into sites, and each site is scored in terms of its marginal conservation value, that is, the incremental value added to the current system of conservation lands by making the next conservation investment in that site. Site prioritization depends on the farmland resources the site contains, the threat to those resources, and the conservation cost of mitigating that threat. The strategic objective is to allocate conservation funds among a set of candidate sites such that there is the greatest possible farmland value remaining at the end of the planning period. We demonstrate the framework for preservation of farmlands in the Bay Area/Delta Bioregion. Because the criteria for measuring objectives 2 and 3 require spatial and nonspatial data that are not readily available statewide or even for a bioregion, we only develop and demonstrate the framework for objective 1. Existing data are used to map resource values and threats to arrive at maps of marginal conservation value without consideration of site cost. We use a crude estimate of the cost of conservation easements to demonstrate how the framework could then be used to prioritize conservation investments subject to a fixed budget.
Keywords: Bay Delta bioregion; California Legacy Project; conservation planning; cost-effectiveness; farmland preservation; GIS; marginal value